Sustainability of Local Public Finances from the Perspective of Territorial Disparities in the Rural Areas of Romania - Marinela Istrate; Ionel Muntele (Land)
The sustainability of local public finances is of general interest in the context of the socio-economic transformations of recent decades. In former communist countries such as Romania, where there has been no real reform of local government, this interest is heightened by the strong disparities between administrative units that have adapted to the new context and those that, for various reasons, have become dependent on government subsidies to be able to function. Using information derived from the budget execution for 2019–2023 at the level of the administrative units in rural areas, this study analyzes the structure of income and expenditure budgets. The territorial disparities are demonstrated by typological analyses showing strong regionalization, with a well-defined income or expenditure structure profile. In the same sense, multivariate analysis which uses a series of illustrative demographic and socio-economic profiles as explanatory variables shows significant correlations with the structure of local budgets. It is thus possible to distinguish certain regional patterns, depending on the level of development, geographical position, or quality of infrastructure. The study results demonstrate the need for genuine administrative reform to reduce the dependence of local budgets on subsidies and increase their self-sustainability, especially in rural areas.